Endothelial factors and stroke risk in pediatric sickle cell anemia patients: insights from VCAM1 and ITGA4 variants - Silva, Marisa (2017)
Sickle cell anemia (SCA) arises from homozygosity for the mutation c.20A>T in the HBB gene which originates hemoglobin S (HbS). In hypoxic conditions, HbS polymerizes inside erythrocytes deforming them and ultimately leading to hemolysis and vaso-occlusion. SCA shows a multifactorial-like behaviour with a high heterogeneity of clinical features, with stroke being the most severe of them. This heterogeneity may arise from underlying genetic modifiers, namely those affecting vascular adhesion/endothelial dysfunction. These include genes encoding the VCAM-1 molecule and its ligand VLA-4 (ITGA4 or integrin α4), increasingly studied due to their expression in activated human endothelium and leucocytes/stress reticulocytes, respectively. The aim of this study was to identify putative genetic modulators of stroke risk by analyzing 70 pediatric SCA patients, grouped according to their degree of cerebral vasculopathy. Molecular analysis was performed using Next-Generation Sequencing (NGS) and Sanger Sequencing. R software was used for statistical analyses and association studies. In silico studies were performed using PHASE, TFbind, PROMO and Human Splicing Finder software tools. We identified six different VCAM1 promoter variants and seven haplotypes. The VCAM1 promoter rs1409419_T allele was associated with stroke events (p=0.008; O.R.= 4.33; C.I.95% =1.391-14.257), while one VCAM1 promoter haplotype was found to be protective of stroke (p=0.011; O.R.=0.22; C.I.95% =0.048-0.784). On the ITGA4 gene, forty variants were found, six of them novel. All patients presented with at least one variant in this gene. We observed co-inheritance of specific sets of ITGA4 variants indicating the presence of haplotypes not previously described. Additionally the presence of specific variants seems to result in a predisposition for either high reticulocyte count, elevated lactate dehydrogenase, raised bilirubin levels or increased transcranial Doppler velocity values. Our results reinforce the role of endothelial molecules and blood cell interaction in SCA severity. The association between specific VCAM1, as well as ITGA4, variants with certain cerebral vasculopathy predictors, further enhances their putative modulating effect on pediatric stroke severity and prognosis. These findings provide additional clues on the SCA pathophysiology and uncover features of both genes that may prove to be crucial as potential therapeutic targets.